2015
DOI: 10.1120/jacmp.v16i2.5227
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a general‐purpose, actively scanned proton beamline for ocular treatments: Geant4 simulations

Abstract: The Italian National Center for Hadrontherapy (CNAO, Centro Nazionale di Adroterapia Oncologica), a synchrotron‐based hospital facility, started the treatment of patients within selected clinical trials in late 2011 and 2012 with actively scanned proton and carbon ion beams, respectively. The activation of a new clinical protocol for the irradiation of uveal melanoma using the existing general‐purpose proton beamline is foreseen for late 2014. Beam characteristics and patient treatment setup need to be tuned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“… 57 Another alternative could be the use of synchrotron‐based facilities. 15 , 58 , 59 , 60 Ciocca et al 15 reported that a constant pulsed proton beam with energy set to around 70 MeV without degrading the beam has led to LPs between 1.40 and 1.70 mm for various geometry‐shaped FSs between 6 and 25 mm. However, the reported treatment time was up to 3 min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 57 Another alternative could be the use of synchrotron‐based facilities. 15 , 58 , 59 , 60 Ciocca et al 15 reported that a constant pulsed proton beam with energy set to around 70 MeV without degrading the beam has led to LPs between 1.40 and 1.70 mm for various geometry‐shaped FSs between 6 and 25 mm. However, the reported treatment time was up to 3 min.…”
Section: Discussionmentioning
confidence: 99%
“…Even a small gain has a clinical impact, as the LP is still the primary parameter to spare organs‐at‐risk 57 . Another alternative could be the use of synchrotron‐based facilities 15,58‐60 . Ciocca et al 15 reported that a constant pulsed proton beam with energy set to around 70 MeV without degrading the beam has led to LPs between 1.40 and 1.70 mm for various geometry‐shaped FSs between 6 and 25 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The use of scanning systems for ocular applications is a developing application, 3 as are scanned proton mini-beams, 4 and both are outside the scope of this report. Also, the The non-attenuating opening in a collimator, shaped irregularly according to the shape of the target, that allows radiation to reach a target Collimator Beam A group of particles or rays traveling in the same direction in parallel or diverging from a point Beam energy…”
Section: Purpose and Scope Of This Reportmentioning
confidence: 99%
“…The use of scanning systems for ocular applications is a developing application, 3 as are scanned proton mini‐beams, 4 and both are outside the scope of this report. Also, the radiobiological aspects of proton therapy are covered by the dedicated TG‐256 5 …”
Section: Purpose and Scope Of This Reportmentioning
confidence: 99%
“…A preliminary study based on Monte Carlo (MC) simulations showed that the starting strategy of minimizing air gaps among patient skin (ocular globe), range shifter (RS) and nozzle, which is commonly valid for conventional proton therapy, lead to very poor results, in terms of unacceptable lateral beam penumbra width, even in the presence of a field‐specific ocular collimator . That finding led us to investigate completely different approaches, as reported in this work.…”
Section: Introductionmentioning
confidence: 97%